The First All-Union Turkological Congress: repressed and shot executed - Abytov , Байболот (Turkic Studies Journal, 2023)
In the article we made an attempt to study the primary sources of the history of the First All-Union Turkological Congress, which was held from February 26 to March 5, 1926, in the city of Baku. In this case, we have verbatim reports of the congress, which until recently were inaccessible to a wide range of researchers, relatives and descendants of the participants in that very congress, and we also have a number of other materials regarding participants from the Kyrgyz Autonomous Region within the RSFSR. In fact, it was the first official congress, the main issue of which was the transition from the Arabic script to the Latin alphabet, in all the Turkic republics and peoples of the USSR. Of course, the Azerbaijan SSR was the initiator of the latinization of the writing of the Turkic peoples of the USSR. Unfortunately, many of the current generations of young people of the Turkic-speaking countries and peoples of the CIS, especially among philologists and historians, know practically very little about the First Congress - the Kurultai of Turkologists. Therefore, this article is devoted specifically to the first congress of Turkologists in Baku, which was held almost a hundred years ago. It was the kurultai, which laid the foundation for the new national writing of many Turkic peoples, not only in the USSR, but in other countries of the world. However, this congress remained in history as a congress of repressed and executed delegates, scientists-turkologists, educators and government officials who took part in that famous congress. A vivid proof of this is our materials in this article.